Setting thresholds is not enough: Beach litter as indicator of poor environmental status in the southern Adriatic Sea. (April 2022) - Mandić, Milica; Gvozdenović, Slađana; De Vito, Doris; Alfonso, Giuseppe; Daja, Shkelqim; Ago, Besnik; Cela, Eralba; Ivanović, Aleksandra; Zoto, Alba; Malovrazić, Nemanja; Beli, Elena; Ingrosso, Gianmarco; et al.
Abstract: This study deals with the issue of beach litter pollution in the context of the Descriptor 10 of the Marine Strategy Framework Directive Good Environmental Status of EU waters and Ecological objective 10, Common indicator 22 of IMAP. Analyses of the amount, distribution and categorization of beach litter were conducted on nine beaches during 108 surveys covering the area of 206.620 m 2 in Albania, Italy and Montenegro. Our findings showed that the level of beach litter pollution on south Adriatic beaches is significantly above the adopted threshold values, with a median item numbers of 327, 258 and 234 per 100 m of beach stretch for Albania, Italy and Montenegro, respectively. It can be concluded that, when it comes to beach litter pollution, GES has not been achieved. Given the defined baseline and threshold values at the EU level, the process of reducing the total amount of marine litter in southern Adriatic Sea will be very challenging and needs urgent and specific actions. Highlights: The level of beach litter on south Adriatic beaches is significantly above the adopted threshold values. Average litter abundance was 327.42, 258.2 and 234.5 per 100 m of beach stretch. Artificial polymer material was predominant in all study areas in terms of number of items and weight. The process of reaching GES will be very challenging and needs urgent and specific actions. Good Environmental Status (GES) has not been achieved in South Adriatic beaches.